The Medial Plantar Flap Vascularized by the Reverse Flow Lateral Plantar Artery: A Novel Variation through the Case of Aggressive Digital Papillary Adenocarcinoma of the Sole - Hayashi, Ayato; Matsumura, Takashi; Horiguchi, Masatoshi; Komuro, Yuzo; Itoh, Munenari; Idezuki, Takeo; Igarashi, Atsuyuki; Mizuno, Hiroshi (Journal of Reconstructive Microsurgery, 2012)
Aggressive digital papillary adenocarcinoma (ADPA) is a rare neoplasm of eccrine sweat gland origin that typically presents as a mass on the distal extremities. It is associated with high rates of local recurrence and distal metastasis. Presented here is the case of a 61-year-old male who developed ADPA on his distal sole just above the head of the first metatarsal bone. Wide excision of the tumor involving a 3-cm skin margin from previous surgical scar of biopsy was performed, and sentinel lymph node biopsies were taken from the popliteal fossa and inguinal regions. During this wide excision surgery, the pedicle for the reverse medial plantar flap had to be removed along with the tumor. Reconstructive surgery was performed with a medial plantar flap that was vascularized with a lateral plantar artery in a reverse fashion. This flap successfully covered the defect and the patient can walk without any problems. However, the pedicle crossed the donor site somewhat tightly and the flap became congested for a while. Therefore, it is important to ensure careful handling of the donor site when performing this procedure.
Keywords: aggressive digital papillary adenocarcinoma; medial plantar artery flap; foot reconstruction; sweat gland tumor; reverse flow flap